Do all patients with acquired methemoglobinemia need treatment? A lesson learnt - Raju Khanal; Paras Karmacharya; Ranjan Pathak; Dilli Ram Poudel; Sushil Ghimire; Richard Alweis (Greater Baltimore Medical Center, 2015)
Acquired methemoglobinemia is a medical emergency, and its prompt recognition and treatment can avoid catastrophic complications including death. However, in mild asymptomatic cases without any comorbid conditions, it would be reasonable to simply observe and treat symptomatically to avoid severe treatment-related complications, especially in patients with suspected glucose-6-phosphate dehydrogenase (G6PD) deficiency. We present a case of mild methemoglobinemia in occult G6PD deficiency in which the patient developed hemolysis after treatment with intravenous methylene blue, requiring transfusion.